Primary Energy Resources and Environmental Impacts of Various Heating Systems Based on Life Cycle Assessment - Viktoria Mannheim; Károly Nehéz; Salman Brbhan; Péter Bencs (Energies, 2023)
This paper utilizes a life cycle assessment (LCA) to evaluate three heating systems’ energy resources and environmental impacts. The first system uses an electric heat pump that exclusively relies on geothermal energy. The second system operates on a gas boiler system that utilizes non-renewable electricity and natural gas. Lastly, the third system incorporates an absorption heat pump utilizing geothermal energy and natural gas. In the first step, cradle-to-gate assessments were prepared for the renewable, conventional, and mixed systems. The second step involved comparing the system scenarios based on their loads and energy resources. Primary energy, material resources, emissions, and impact categories were normalized and weighted using the CML, ReCiPe, and EF 3.0 methods. Finally, models for environmental reliability and complex decision support were developed. The novelty of this research lies in analyzing the ecological burden and energy usage of a mixed energy system that incorporates both renewable and non-renewable energy sources. The results show that the gas boiler system has a higher load, primarily due to the depletion of abiotic fossil fuels. However, the acidification is higher when an electric heat pump is used. The absorption heat pump system falls between the renewable and conventional systems in terms of both fossil depletion and acidification.